2014
DOI: 10.1061/(asce)ae.1943-5568.0000136
|View full text |Cite
|
Sign up to set email alerts
|

Gravity and Wind Load Path Analysis of a Light-Frame and a Traditional Timber Frame Building

Abstract: The objective of this study was to compare structural load path and system behavior of a light-frame (LF) and a timber frame (TF) structure. This load path analysis is part of a broader research effort that compares LF to TF residential structures. Structural analysis software was used to create a model of each structure. The TF structure was composed of large-dimension timbers and structural insulated panels (SIPs). An equivalent LF structure was designed for comparison, following the guidelines of the Intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The first is the horizontal vibration along the depth direction, the second is the horizontal vibration along the width direction, and the third is the torsional vibration. The frequency of the depth-direction vibration is slightly smaller than that of the width-direction vibration, which (10) means that the depth-direction stiffness is smaller than the width-direction stiffness.…”
Section: Modal Analysismentioning
confidence: 93%
See 1 more Smart Citation
“…The first is the horizontal vibration along the depth direction, the second is the horizontal vibration along the width direction, and the third is the torsional vibration. The frequency of the depth-direction vibration is slightly smaller than that of the width-direction vibration, which (10) means that the depth-direction stiffness is smaller than the width-direction stiffness.…”
Section: Modal Analysismentioning
confidence: 93%
“…Zisis [9] studied the wind-induced vibration performance of residential timber buildings normally seen in North America with experimental and numerical methods. Malone et al [10] established an FEM of a local timber building with pinned connection joints with the software SAP2000 (Structural Analysis Program 2000) and achieved force-transferring paths under wind action. In the study presented by Morrison [11], particular attention was given to the failure modes of a low-rise building during a wind tunnel test.…”
Section: Introductionmentioning
confidence: 99%
“…Lala et al [41] compared the seismic performance of different types of bamboo-footed buildings in northeast India. Some other studies have explored the structural performance of low-rise wooden structures and masonry buildings based on different case studies [42][43][44][45][46].…”
Section: Methodsmentioning
confidence: 99%
“…In both studies, the sheathing panels were considered as continuous in their models ignoring sheathing gap, and the effect of sheathing nails was incorporated into the wall and roof panels by adjusting the sheathing's shear modulus. Their modeling methods were later used by Malone et al [126] to compare the structural load path of a timber frame (TF) and a light-frame (LF) structure. It was found that TF outperformed the LF in both resisting uplift and story drift because continuous posts resisted out-of-plane wind loading more effectively than platform-framed exterior walls did, and the structural insulated panels used in the TF had greater stiffness compared with the LF shear walls.…”
Section: Fig 3 Modeling Methods Used For Structural Components In Pmentioning
confidence: 99%